2006
DOI: 10.1111/j.1743-6109.2006.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Scarless skin repair in immunodeficient mice

Abstract: Scarring, the end result of the wound healing process in adult mammals, is a problem of significant clinical importance. We observed that athymic nude-nu mice, similar to mammalian fetuses, are able to restore the structure and integrity of injured skin through a process resembling regeneration, where scar formation is absent. Among the postinjured skin tissues collected from athymic nude-nu, wild-type controls (C57BL/6J), severe-combined immunodeficient, Rag (lack of B and T cells), athymic (thymectomized neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
121
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(138 citation statements)
references
References 52 publications
(94 reference statements)
9
121
0
8
Order By: Relevance
“…Earlier studies [18,19] suggest that delayed T-cell infiltration along with decreased T-cell concentration in the wound site is associated with impaired wound healing, while others have reported that CD4+ cells (T-helper cells) have a positive role in wound healing and CD8+ cells (T-suppressor-cytotoxic cells) play an inhibitory role in wound healing. Interestingly, recent studies in mice deficient in both T-and B-cells have shown that scar formation is diminished in the absence of lymphocytes [20]. In the light of these findings, we conclude that microbial infections and glycosuria are major factors contributing to prolonged healing orthopaedic wounds in Imo State, south eastern Nigeria.…”
Section: Resultssupporting
confidence: 56%
“…Earlier studies [18,19] suggest that delayed T-cell infiltration along with decreased T-cell concentration in the wound site is associated with impaired wound healing, while others have reported that CD4+ cells (T-helper cells) have a positive role in wound healing and CD8+ cells (T-suppressor-cytotoxic cells) play an inhibitory role in wound healing. Interestingly, recent studies in mice deficient in both T-and B-cells have shown that scar formation is diminished in the absence of lymphocytes [20]. In the light of these findings, we conclude that microbial infections and glycosuria are major factors contributing to prolonged healing orthopaedic wounds in Imo State, south eastern Nigeria.…”
Section: Resultssupporting
confidence: 56%
“…Tissue repair cycles are monitored by a sequence of biochemical and cell events organized to restore the tissue integrity after the lesion. There is participation of the immune system acting in the protection of injured tissues against possible infections and in the secretion of growth factors such as cytokines, which metabolically change the morphological state of animal tissues (Park & Barbul, 2004;Gawronska-Kozak et al, 2006). Oral supplementation of NaCl decreases CK activity, but whether the inhibition of mdx muscle degeneration occurs before fiber necrosis remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was shown that epidermal Notch recruits a subset of inflammatory cells in the postwounding dermis in a non-cellautonomous way (49). It was assumed that that immunological defect does not have a direct impact on the mechanism of wound healing in nude mice (50). However, earlier studies showed that T-cell deficiency in the skin of nude mice leads to enhanced breaking strength and collagen deposition, which were reduced to the values observed in wild-type controls when syngeneic T lymphocytes were reconstructed (51).…”
Section: Foxn1 Involvement In Signaling Pathwaysmentioning
confidence: 99%
“…The skin of Foxn1-deficient mice is thicker and hyperplastic (16), exhibits distinctive biochemical and physical characteristics (50), and in general, seems to display immature embryonic features (17). It was reported that the spatiotemporal expression pattern of specific keratins in the IFE of nude mice is altered.…”
Section: Nude Mice (Foxn1 Deficient) From the Skin Point Of Viewmentioning
confidence: 99%
See 1 more Smart Citation